DMOSYS: defect-monitoring system for building maintenance at polytechnic - Ismail, Zul-Atfi (2013)
Maintenance management could be a complex subject if implementation and planning issues of the building facility are not handled properly. In this context, the current maintenance management method has affected the efficiency of the building facility management at Polytechnics. Many issues such as poor service delivery, inadequate finance, poor maintenance planning and maintenance backlogs were emerged due to the usage of conventional method application (paper-based form and unsystematic database). Therefore, this research is to review existing maintenance management practices, and subsequently develop a prototype system based on the stated problems related to the conventional method in improving the maintenance management processes. Literature review and semi-structured interview was carried out to achieve the objectives. Eight Polytechnics are selected based on major problems of using conventional method in the comparison to investigate the maintenance management practices in each Polytechnic. There are around 32 Polytechnics in Malaysia and almost are using conventional methods. The number is considered very big indicating that the use of modern Information and Communication Technology (ICT) is still very limited compared to other institutions of higher learning in Malaysia. The results revealed that the practice of maintenance management at Polytechnics needs to be improved and a computerised system was proposed based on the requirements of a maintenance management system identified through the case studies. The framework was encapsulated in a computer-based prototype system based on Microsoft Visual Basic.Net as a graphical user-interface while for the database design, the Microsoft Access is used to deploy the information for maintenance management processes. The computerised system was developed using Data Flow Diagram (DFD) and coding. Subsequently, the prototype system was tested by running it until the critical problems were fixed and its functional requirements work correctly. This system will help with the building diagnosis and decision making process approaches. It will assist staff in facilitating the maintenance identification, assessment, planning and execution in relation to building facility. In conclusion, the developed prototype system can improve the maintenance management practices effectiveness for building facility to provide highquality building facility for safe and healthy environment.